1994
DOI: 10.1001/archpsyc.1994.03950120061010
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-up of Psychotherapy and Pharmacotherapy for Cocaine Dependence

Abstract: Our findings suggest a delayed emergence of the effects of cognitive-behavioral relapse prevention, which may reflect the subjects' implementation of the generalizable coping skills conveyed through that treatment. Moreover, these data underline the importance of conducting follow-up studies of substance abusers and other groups because delayed effects may occur after the cessation of short-term treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
231
5
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(272 citation statements)
references
References 21 publications
29
231
5
7
Order By: Relevance
“…The program consisted of six lessons, or modules, the content of which was based closely on a NIDA-published CBT manual (38) used in several previous randomized controlled trials in a range of substance-using populations (6,39,40). The modules covered the following core concepts: (1) understanding and changing patterns of substance use, (2) coping with craving, (3) refusing offers of drugs and alcohol, (4) problem-solving skills, (5) identifying and changing thoughts about drugs and alcohol, and (6) improving decision-making skills.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The program consisted of six lessons, or modules, the content of which was based closely on a NIDA-published CBT manual (38) used in several previous randomized controlled trials in a range of substance-using populations (6,39,40). The modules covered the following core concepts: (1) understanding and changing patterns of substance use, (2) coping with craving, (3) refusing offers of drugs and alcohol, (4) problem-solving skills, (5) identifying and changing thoughts about drugs and alcohol, and (6) improving decision-making skills.…”
Section: Treatmentsmentioning
confidence: 99%
“…Despite evidence of positive and durable outcome (6,7), CBT remains rarely implemented in the range of settings where individuals with substance use disorders are treated (8). There are a number of obstacles to delivering CBT and other empirically validated therapies in clinical practice, including the limited availability of professional and specialty training programs that provide high quality training, supervision and certification in CBT (9), high rates of clinician turnover and lack of a CBT-trained workforce in many treatment settings (10)(11)(12), the relative complexity and cost of training clinicians in CBT (13,14), as well as high case loads and limited resources.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that, at T2, participants did not have time to observe their new behaviour patterns or to practise the learnt strategies. Accordingly, long-term positive outcomes of CBT without immediate effects have been reported in the non-neurological population and attributed to the generalisation of acquired strategies (Carroll et al, 1994). However, previous studies using CBT protocols for managing anger in the TBI population have found immediate effects of intervention, with assessments carried out between zero and three weeks after the completion of the programme (Hart et al, 2012;Walker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, estudos internacionais que avaliam a eficácia desse tipo de programa têm sido realizados e revelam que dependentes químicos podem permanecer várias semanas consecutivas em abstinência, através da intervenção com as linhas telefônicas de ajuda [45][46][47] . Também há demonstração de que os pacientes podem requerer cuidados menos intensivos do que após intervenções do tipo face a face 48 51 .…”
Section: Discussionunclassified